FACEBOOK-BASED WRITING INSTRUCTIONAL MATERIAL IN ENGLISH CLASS: LECTURERS’ PERCEPTION - Geminastiti Sakkir; Syarifuddin Dollah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2019)
The study attempted to explore lecturers’ perceptions on the use of Facebook-based writing material in English class at STKIP Muhammadiyah Rappang, South Sulawesi, Indonesia. The present study was a part of research and development (R&D). There were two writing lecturers of the English Education Department in 2016/ 2017 as the subject of the study. The data gained from the questionnaires of the lecturers’ perception on the implementation of Facebook-based instructional material in English writing class using the Likert scale. The scoring system was done positive and negative statement score. The data have been analysed descriptively by using the frequency and percentage. It aimed to measure the lecturers’ opinion. To interpret the lecturers’ responds, the researchers used the interval estimation. The interval estimation was applied to measure the parameter of population based on the score of interval rates which ranged to 4 categories level. The results found that the lecturers agree that the content of learning English writing by using Facebook-based instructional materials are suitable for the students’ level, their need for learning and their daily lives. The average score of lecturers’ perceptions is 3.4 which indicates that from the four components of the product (content, language, presentation and graphic) overall shows suitability to the writing English material and to the students. It means that the implementation of Facebook-based instruction in teaching writing is interesting for the lecturers. It was proved by the results of the lecturers’ perception